2007
DOI: 10.1108/17511060710837427
|View full text |Cite
|
Sign up to set email alerts
|

Regional brand image and perceived wine quality: the consumer perspective

Abstract: Adult articular cartilage exhibits little capacity for intrinsic repair, and thus even minor injuries or lesions may lead to progressive damage and osteoarthritic joint degeneration, resulting in significant pain and disability. While there have been numerous attempts to develop tissue-engineered grafts or patches to repair focal chondral and osteochondral defects, there remain significant challenges in the clinical application of cell-based therapies for cartilage repair. This paper reviews the current state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
203
4
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(226 citation statements)
references
References 66 publications
7
203
4
2
Order By: Relevance
“…Apart from the price, studies on wine consumption often define quality as a superior but difficult to recognize reason for purchasing wine (Saenz-Navajas et al, 2013;Johnson and Bruwer, 2007;Verdú Jover et al, 2004). Several researchers have examined the various components of wine quality, mainly divided into intrinsic and extrinsic dimensions, whereby the product complexity led to concentrate on perceived and less on actual quality (Smith and Bentzen, 2011;Masson et al, 2008; Crossgenerational preferences for wine Pettigrew, 2007).…”
Section: Development Of Hypothesesmentioning
confidence: 99%
“…Apart from the price, studies on wine consumption often define quality as a superior but difficult to recognize reason for purchasing wine (Saenz-Navajas et al, 2013;Johnson and Bruwer, 2007;Verdú Jover et al, 2004). Several researchers have examined the various components of wine quality, mainly divided into intrinsic and extrinsic dimensions, whereby the product complexity led to concentrate on perceived and less on actual quality (Smith and Bentzen, 2011;Masson et al, 2008; Crossgenerational preferences for wine Pettigrew, 2007).…”
Section: Development Of Hypothesesmentioning
confidence: 99%
“…Regarding "New World" wine countries such as Australia or USA, where grape varietal marketing has played a significant role in consumers' purchase processes, ROO is also gaining importance in wine marketing since the end of 1990´s (Bruwer & House, 2003;Johnson & Bruwer, 2007). The importance of the ROO effect in these markets has been analysed by various authors.…”
Section: Introductionmentioning
confidence: 99%
“…Bruwer & House (2003) found that ROO ranked third behind price and grape variety/wine style in Australian consumers' wine purchase intention in a retail outlet. According to Johnson & Bruwer (2007), the wine's region is the most important quality-predicting information on wine labels in the California market, with over 85% of consumers taking the region into account when evaluating a wine label. Indeed the region was the most often reported source of information, above brand, vintage, appellation, state, or country.…”
Section: Introductionmentioning
confidence: 99%
“…Regional brands should aim to express the identity of the winemaking region that is, by nature, encapsulated in the wine because of the strong link between the physical characteristics of the territory and the grapes (Carlsen, Dowling and Cowan, 1997). On the consumer side, it has been demonstrated that the regional brand is an important cue for wine evaluation (Rasmussen and Lockshin, 1999;Thomas and Pickering 2005;Johnson and Bruwer, 2007); the development of a regional wine brand has been particularly rewarding for red wines (Schamel, 2006) and for small winemaking regions that have the typical structure of a "discovery market," as defined by Christy and Norris (1999: 806). Although the wines of individual producers have a high potential for differentiation, it is difficult for those brands to emerge from the fray, given the cost of broadbased marketing and communication.…”
mentioning
confidence: 99%
“…Another example of regional collective branding coordinated by associations is that of Spanish winemaking regions, like La Rioja, that followed a two-step approach: first, the creation and communication of the collective regional brand, followed by company brands that exploited the halo of the regional brand's reputation (Gil and Sanchez, 1997). Australia has also seen a shift from national branding to regional branding (Johnson and Bruwer, 2007) in which, absent a system of appellations, the focus of associations is on coordination and marketing strategies to create awareness of the regional brand, especially in export markets (Phillips, 1992;Rasmussen and Lockshin, 1999;Turner and Creasy, 2003).…”
mentioning
confidence: 99%